A qualitative descriptive (QD) analysis of community-level experiences of healthcare delivery in rural, post-structural adjustment Ghana - Courtney Queen; Derick N. Boakye (Elsevier, 2022)
Structural adjustment programs (SAPs) imposed in Ghana during the 1970s intentionally stratified the country without recognition of the diverse methods of healing commonly relied on by communities. Development assistance programs forced the restructuring of all major institutions and especially the organization of health care. This restructuring changed the cost structure for health care and while intending to increase access and geographic availability, SAPs resulted in the further marginalization of rural communities-exacerbating existing circumstances and further stratifying this society. The focus of this study was to capture key aspects of different types of healthcare delivery in a rural community and to learn more about their disease or illness specialties and treatment approaches. With a qualitative design (QD) approach, and based on fourteen walking interviews, this paper offers insight into seven different ways by which members of otherwise marginalized communities may access healthcare.